PENERAPAN PAJAK PENGHASILAN (PPH) FINAL TERHADAP USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERDASARKAN PP NO 46 TAHUN 2013 - Deddy Dariansyah S (Sosio e-Kons, 2016)
With the issued Government Regulation (PP) No. 46 Year 2013 on the final tax that specifically apply to businesses small and medium businesses and certain businesses, which regulates the treatment of Income Tax (PPH) final that has gross income derived by the taxpayer from the business the amount of up to USD 4.8 billion in one year, quite worn Final Income Tax 1% each month. Data from the Tax Office Primary Kramat Jati 2016, the amount of taxpayer's gross income certain categories of business 4804, then the number of the individual taxpayer 4,371 people. of the data Taxpayer SMEs is appropriate to implement Government Regulation No. 46 Year 2013 on Income Tax Final 1% of the calculation of gross income each month, so that the taxpayer can get the facility of Final Income Tax, to apply for a certificate of free (SKB) on deduction / collection of tax at the Tax Office Kramat Jati registered as a Small Business Tax Payer.Keywords: government regulation, PPH Final, Small Medium Enterprise